Obstructions of prosthetic heart valves: diagnosis and treatment considerations - Karabulut, Mehmet Nuri; Günay, Rafet; Demirtaş, Mahmut Murat (The European Research Journal, 2024)
Objectives: Since the first years of native heart valve replacement by - prosthetic valves; prosthesis thrombogenicity has kept its importance as a serious problem causing post-operative morbidities and mortality. This study aims to evaluate early postoperative morbidity and mortality of patients diagnosed with prosthetic valve thrombosis and treated surgically or non-surgically. Methods: Thirty-one patients diagnosed with and treated for prosthetic valve thrombosis were evaluated retrospectively. The patients were followed up for 58 months. Results: There were 24 females and 7 males. The mean patient age at the time of prosthetic valve thrombosis diagnosis was 40.7±11 (range, 10-57) years. The mean duration between prosthetic valve replacement and the first signs of prosthetic valve thrombosis was 67.67±66 (range, 1 to 300) months. All patients presented with a functional capacity of NYHA Class III or IV. A total of 32 interventions; 27 surgical and 5 thrombolytic treatments due to elevated aortic prosthetic valve pressure gradient which did not improve with thrombolysis. Of 27 surgical interventions for thrombosed prosthetic valves, 21 involved mitral, 2 aortic, and 4 tricuspid positions. A total of 9 patients died during follow-up. The overall mortality rate was 29.03%. The mortality rate was 29.62% after surgical interventions and 20% after thrombolytic treatment. Conclusion: Currently prosthetic valve replacement is the basic palliation method in the management of patients with diseased native heart valves. In the majority of mechanical prosthetic valve obstructions, the main pathology is fibrous tissue proliferation-related to irregular warfarin usage, which in turn causes the development of acute symptoms secondary to acute valve thrombosis. The necessary treatment method for prosthetic valve obstructions should be either the use of thrombolytic agents or the replacement of the obstructed prosthetic valve with a new one.